Pemanfaatan Larva Magot Dalam Penyusunan Ransum Pakan Puyuh Petelur Di Desa Amadanom Kecamatan Dampit Kabupaten Malang - Suroto, Karunia Setyowati; Djoko, Riyanto (Universitas Islam Kadiri, 2024)
Quail farming is a promising micro business with affordable start-up capital and small land area. Quail eggs have high health value and culinary potential. Quail meat is nutritious, their droppings can be used as fertilizer, and their feathers can be made into crafts. Quail can produce up to 300 eggs per year. However, the COVID-19 pandemic and rising feed prices have made it difficult for many farmers. Maggot larvae from the black soldier fly are an economical feed alternative. This study aims to utilize maggot larvae as an economical feed source for laying quail. This research is entitled